Role of hybrid imaging techniques like PET-MRI or PET-CT - Dalal Abdullah Hawisawi; Asrar Mustafa Alyamany; Bashayer Hameed Alrowithy; Ibrahim Mugead Alotaibi; Omar Ahmed Saeed Alhani; Bandar Nasser Olyan Almutairi; Sharifah Mohammad awad; Nada Amjad Kemawi; Hani Abdulrahman Alhazmi; Faisal Ali Alharthy; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The goal of hybrid imaging is to improve diagnosis accuracy by combining two imaging modalities that give complementary functional and anatomical information in a single scan. By facilitating exact diagnosis, monitoring, and tailored treatments, these innovations are revolutionizing personalized medicine. Aim:to improve diagnostic accuracy, patient care, and treatment planning, hybrid imaging integrates functional and anatomical information into a single diagnostic modality. Conclusion:By merging the advantages of functional and anatomical imaging, hybrid imaging techniques such as PET-CT and PET-MRI constitute a notable step forward in contemporary diagnostic medicine. PET-CT has long been used in the fields of oncology, cardiology, and neurology; however, PET-MRI is especially useful in pediatric and neuro-oncological settings due to its reduced radiation dose and better contrast for soft-tissue imaging.The use of these modalities allows for more precise diagnoses, more precise illness detection, and more in-depth information for tailoring treatment plans to each individual patient. With the rapid advancement of technology, hybrid imaging is set to make an even bigger impact in the field of precision medicine, leading to better patient outcomes.